Look at yourself: Concerning affectation as a key mechanism of curricular reform policies - Villagran, Carla Andrea (Education Policy Analysis Archives, 2018)
This article presents the results of a research project that seeks to describe and analyze the curricular policies of reform in the daily life of schools, paying particular attention here to the processes of regulation and self-regulation that they produce and impose on their subjects. From the Foucauldian notion of governmentality we understand that curriculum policies and regulations, technologies, and behaviors produce performative effects (Ball, 2002, 2012), which affect not only the life of the institutions but also of the subject (Ahmed, 2004, Berlant, 2011). Thus, the question that orientates this article is woven around the articulation of the government of others and self-government (Foucault, 1988, 2009) as a key mode of school reform technologies and the modes of social affectation. The processes of reform cross subjects through performative technologies (Ball, 2002) and constitute a part of what Rose (2012) called the ethopolytic, that is, these processes act at the level of feelings and beliefs, and put the self in check. As a hypothesis, it is argued that judgment, self-reflection and self-responsibility are attached to questions that teachers ask themselves in the call to become better than they are.